2013
DOI: 10.1007/s00436-013-3347-x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of cestodes in Artemia spp. throughout the annual cycle: relationship with abundance of avian final hosts

Abstract: Brine shrimp, Artemia spp., act as intermediate hosts for a range of cestode species that use waterbirds as their final hosts. These parasites can have marked influences on shrimp behavior and fecundity, generating the potential for cascading effects in hypersaline food webs. We present the first comprehensive study of the temporal dynamics of cestode parasites in natural populations of brine shrimp throughout the annual cycle. Over a 12-month period, clonal Artemia parthenogenetica were sampled in the Odiel m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 42 publications
4
27
2
Order By: Relevance
“…The present study, conducted during a full year, is the most exhaustive investigation of parasite infection in A. franciscana to date. In contrast to similar studies of native Artemia (Sánchez et al 2013b), parasite infection was consistently low throughout the year, suggesting that parasites have a crucial role in the competitive success of this highly invasive species.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The present study, conducted during a full year, is the most exhaustive investigation of parasite infection in A. franciscana to date. In contrast to similar studies of native Artemia (Sánchez et al 2013b), parasite infection was consistently low throughout the year, suggesting that parasites have a crucial role in the competitive success of this highly invasive species.…”
Section: Discussioncontrasting
confidence: 99%
“…However, both studies were based on sampling from limited time periods, and characterisation of the infections in A. franciscana throughout the annual life cycle has not previously been carried out anywhere in the invasive or native range of this New World species. In contrast, a recent study from two sites in southern Spain found consistently high levels of cestode infections in native A. salina (325 km to the east of our study site) and A. parthenogenetica (90 km to the northwest) throughout their annual cycle, which were partly related to the density and biomass of avian definitive hosts (Sánchez et al 2013b).…”
Section: Introductioncontrasting
confidence: 99%
See 3 more Smart Citations